2019
DOI: 10.14744/etd.2019.14892
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxine dosage determination according to Body Mass Index (BMI) after total thyroidectomy

Abstract: Objective: Currently, postoperative thyroid hormone replacement dosing is weight-based with adjustments and made following Thyroid Stimulating Hormone (TSH) values, which may lead to delayed achievement of euthyroidism and failure in achieving an accurate estimation of the levothyroxine dose. We aimed to evaluate the relationship between Body Mass Index (BMI) and Lean Body Mass (LBM) with levothyroxine dose. Materials and Methods: Eighty patients with thyroid disease (benign and malignant) randomly enrolled th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Maghsudi et al compared the efficacy of actual weight, LBM, and BMI based dosing and concluded that BMI had the strongest correlation with LT4 dose and derived a dose calculation formula: Y= -0.013 +0.005 BMI for benign pathology in total thyroidectomy patients (24) . On the other hand, Al-Dhahari et al (25) identified Body Surface Area (BSA) as the most significant predictor and proposed a model accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Maghsudi et al compared the efficacy of actual weight, LBM, and BMI based dosing and concluded that BMI had the strongest correlation with LT4 dose and derived a dose calculation formula: Y= -0.013 +0.005 BMI for benign pathology in total thyroidectomy patients (24) . On the other hand, Al-Dhahari et al (25) identified Body Surface Area (BSA) as the most significant predictor and proposed a model accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TSH levels are increased in patients with obesity, an effect that can be attributed to the leptin hormone produced by adipose tissue. The secretion of T4 and T3 and metabolism of T4 to T3 decreases in healthy elderly patients, although the levels of rT3 increase; the half-life for elimination of T4 can be checked for longer duration (19,20).…”
Section: Levothyroxine and Cholesterol Levelsmentioning
confidence: 99%
“…Toomatari et al investigated the relationship between body weight, BMI, LBM, and the dose of Lthyroxine in patient groups that had undergone total thyroidectomy for benign and malignant thyroid conditions. The authors concluded that BMI is the most favorable parameter, and they also presented new equations for predicting the accurate L-thyroxine dose based on weight, BMI, and LBM (8).…”
mentioning
confidence: 99%